Bladder cancer: features of epidemiology and indicators of specialized care delivery - Saidakova , N.O.; Yatsina , О.І.; Grodzinsky, V.I.; Stus , V.P.; Polion , M.Y.; Shiloh , V.M.; Коnonova, G.E. (Medicni Perspektivi, 2021)
The work is based on the materials of official statistical reporting, the analysis of which was carried out for 10 years, divided into two five-year periods (2009-2013 and 2014-2018). Absolute and intensive rates of morbidity and distribution of bladder cancer of the adult population of Ukraine in the regional aspect, taking into account sex were studied, the basic indicators of the prevalence of pathology were analyzed as well. The revealed unfavorable situation is characterized by a steady increase in morbidity and prevalence at a slower pace during 2014-2018. It is noteworthy the high level of morbidity in men, which is growing against the background of its stabilization among women. At the same time, there was noted the tendency in the reduced number of newly diagnosed patients during professional examinations (in 2018-16.9% against 18.0% in 2014) with diagnosis at stages I-II (72.2% vs. 74.79%), wherein every fifth has stage III-IV. With a tendency to increase in the number of registered patients ≥ 5 years (59.1% vs. 56.5%), the death rate did not change significantly within a year from the time of diagnosis (14.7% vs. 15.6%, respectively). In the structure of specialized care, (65% are patients with the first diagnosis), surgical method accounted for 37-40% by years, the combined was second (up to 20% by years), then radiation and chemotherapy, which together did not exceed 5.0%. Areas with high or low relative rates in relation to the average Ukrainian indicators for all parameters studied were identified. In the presence of regional differences, there is a need for in-depth studies of the state of the issue, including the quality and organization of care.